REPRESENTASI PERBEDAAN KELAS DALAM CERPEN CINTA PERTAMA (CHŪLIÀN) KARYA MO YAN - Egiva Sontiva; Nurni Wahyu Wuryandari (HISKI, 2021)
First Love short story by Mo Yan tells of the first love story of a 9-year-old male student named Jin Tou to a woman who is older than him. The three previous studies that have discussed this short story all emphasize strong intrinsic elements of the story, namely characters and characterizations. They state that the important characters of the story are Jin Tou, Zhang Ruolan and Du Fenyu, Jin Tou's first love is a mixture of innocence, bitterness and happiness played by the boy who has a strange, lonely and unfortunate character. After being traced, and studied using an intrinsic approach and referring to sources outside the short story, it is revealed that the problem discussed in the short story is about class issues represented by each character in the story. The depiction of social class presented is a representation of the problems that have occurred in China. The short story First Love takes place in the history and social conditions of China in the period after the end of the Cultural Revolution and the reopening of schools in China. This short story also presents how Mo Yan as the author sees the conditions after the Cultural Revolution in China as part of the history conveyed through the love story of Jin Tou's character. AbstrakCerpen Cinta Pertama karya Mo Yan menceritakan tentang kisah cinta pertama seorang siswa laki-laki berusia 9 tahun bernama Jin Tou kepada perempuan yang lebih tua darinya. Tiga penelitian terdahulu yang telah membahas cerpen ini semuanya menekankan unsur intrinsik cerita yang kuat, yaitu tokoh dan penokohan. Mereka menyatakan bahwa tokoh penting dari cerita adalah Jin Tou, Zhang Ruolan dan Du Fengyu, cinta pertama yang diraskan oleh Jin Tou adalah campuran dari kepolosan, kepahitan dan kebahagiaan yang diperankan oleh anak laki-laki yang memiliki karakter aneh, kesepian dan malang. Setelah ditelusuri, dan dikaji dengan pendekatan intrinsik dan mengacu pada sumber diluar cerpen, terungkap bahwa masalah yang dibahas di dalam cerpen adalah tentang persoalan kelas yang direpresentasikan oleh masing-masing tokoh dalam cerita. Penggambaran mengenai kelas sosial yang dihadrikan merupakan representasi dari permasalahan yang pernah terjadi di Cina. Cerpen Cinta Pertama mengambil latar sejarah dan kondisi sosial Cina pada periode setelah Revolusi Kebudayaan berakhir dan dibukanya kembali sekolah di Cina. Cerpen ini juga menyajikan bagaimana Mo Yan sebagai penulis melihat kondisi setelah masa Revolusi Kebudayaan di Cina sebagai bagian dari sejarah yang disampaikan melalui cerita cinta tokoh Jin Tou.